PTPN22 polymorphisms associated with type 1 diabetes mellitus in ethnic populations of Russian Federation - O N Ivanova; Sergey Alexandrovich Prokof'ev; Natalia Borisovna Smirnova; Yulia Vladimirovna Tishina; Tatiana Prokop'evna Bardymova; G I Danilova; T V Kovalenko; Elena Vital'evna Titovich; Tamara Leonidovna Kuraeva; Valentina Alexandrovna Peterkova; Ivan Ivanovich Dedov (Сахарный диабет, 2013)
Aim. To evaluate the association of rs2476601 and rs2488457 polymorphisms with type 1 diabetes mellitus (T1DM) in several ethnic populations of Russian Federation and to estimate the cross-populational differences of these polymorphisms.Materials and Methods. A case-control design was applied to study the aforementioned polymorphisms in five ethnic populations of Russian Federation: Bashkir, Yakut, Buryat, Udmurt, Russian. We analyzed DNA samples from 491 patients with T1DM and 408 control subjects. Polymorphisms were identified with RFLP-PCR and RT-PCR. Strength of association was evaluated as odds ratio (OR). All calculations were performed with StatSoft STATISTICA (version 6) and Microsoft Excel 2003 software applications.Results. PTPN22 1858Т+ genotypes were associated with T1DM in Udmurt, Russian and Bashkir populations and PTPN22 1123C+ genotype in Buryat population. We did not find any associations of PTPN22 gene polymorphisms with T1DM in Yakut population. Cross-ethnic comparison of polymorphism frequencies showed statistically significant differences. Allele frequency distribution in Buryat population significantly differs from that of other studied ethnic groups with G-1123C (rs2488457; 71.3%) being a significantly more common finding than C type allele. Russian population of Moscow and Moscow Region is also characterized by higher prevalence of Ttype allele (13%) in C1858Т (rs2476601) polymorphism.Conclusion. Ethnic populations of Asian regions of Russian Federation, characterized by lower rates of T1DM (Yakut and Buryat) demonstrated highest prevalence of G-allele in G-1123C (rs2488457) polymorphism. On the contrary, analyses from Russian population of Moscow and Moscow Region, known to have higher rates of T1DM, suggest higher prevalence of T-allele in C1858Т (rs2476601) polymorphism.